2010
DOI: 10.1124/dmd.110.034421
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism-Based Mathematical Model of Aryl Hydrocarbon Receptor-Mediated CYP1A Induction in Rats Using β-Naphthoflavone as a Tool Compound

Abstract: ABSTRACT:␤-Naphthoflavone (BNF) is a synthetic flavone that selectively and potently induces CYP1A enzymes via aryl hydrocarbon receptor activation. Mechanism-based mathematical models of CYP1A enzyme induction were developed to predict the time course of enzyme induction and quantitatively evaluate the interrelationship between BNF plasma concentrations, hepatic CYP1A1 and CYP1A2 mRNA levels, and CYP1A enzyme activity in rats in vivo. Male Sprague-Dawley rats received a continuous intravenous infusion of vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…ing a 24-h exposure of hepatocytes to BNF and all tested parameters correlated well. The response to BNF in hepatocytes was in agreement with the observation that the induction of hepatic CYP1A1/CYP1A2 mRNA and CYP1A activity in rats in vivo occurred within 2 h after BNF administration (22). A good correlation between the induction of CYP1A1/2 enzyme activities and mRNA expression in human hepatocytes has been also reported (4).…”
Section: B)supporting
confidence: 85%
“…ing a 24-h exposure of hepatocytes to BNF and all tested parameters correlated well. The response to BNF in hepatocytes was in agreement with the observation that the induction of hepatic CYP1A1/CYP1A2 mRNA and CYP1A activity in rats in vivo occurred within 2 h after BNF administration (22). A good correlation between the induction of CYP1A1/2 enzyme activities and mRNA expression in human hepatocytes has been also reported (4).…”
Section: B)supporting
confidence: 85%
“…In order to examine if AhR ligands which activates the canonical AhR pathway demonstrate selective modulation, differential gene expression elicited TCDD, PCB126, β-naphthoflavone (βNF), and indolo-[3,2b]-carbazole (ICZ) was examined in mouse Hepa1c1c7 cells and C57BL/6 liver samples. Although each ligand exhibits high AhR binding affinity, Cyp1a1 mRNA induction and the induction of aryl hydrocarbon hydroxylase activity (Boobis et al, 1977; Chen et al, 1995, 2010; Denison and Nagy, 2003; Denison et al, 2011; Kopec et al, 2008; Pohjanvirta et al, 2002), they are structurally diverse with different metabolism kinetics. Therefore, global gene expression profiles were compared not only to identify conserved differential expression but also to investigate divergent and ligand-specific gene expression changes suggestive of SAhRM activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the plasma concentration of BNF reaches a maximal level at 80-120 min and then starts declining toward a lower plateau value in SD rats given a continuous intravenous infusion of 1.5 or 6 mg/kg/hr BNF for 6 hr (Chen et al, 2010). BNF is known as a substrate of CYP1A enzymes and the BNF clearance increases with time after continuous intravenous infusion to rats (Chen et al, 2010). Such a time-dependent increase in clearance supports the present finding of plasma BNF concentrations not being detected in BNF treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the induction of liver drug-metabolizing enzyme by BNF may affect the metabolism of OPZ in the OPZ+BNF group. It has previously been shown that the plasma concentration of BNF reaches a maximal level at 80-120 min and then starts declining toward a lower plateau value in SD rats given a continuous intravenous infusion of 1.5 or 6 mg/kg/hr BNF for 6 hr (Chen et al, 2010). BNF is known as a substrate of CYP1A enzymes and the BNF clearance increases with time after continuous intravenous infusion to rats (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%